Action Research in a Graduate Foreign Language Teaching Program (1999)
ABSTRACT: This article presents the findings of an investigation on the process of carrying out collaborative action research with teachers of English as a foreign language in a newly created graduate program, in a Colombian university. From the analysis of interviews and minutes of meetings with students and advisors, important issues that impinge on the successful development of the research process were found. The difficulties notwithstanding, participants emphasized the benefits of this experience in terms of empowerment and learning.